# Proving $\frac{1}{n+1} + \frac{1}{n+2}+\cdots+\frac{1}{2n} > \frac{13}{24}$ for $n>1,n\in\Bbb N$ by Induction

Proving $\frac{1}{n+1} + \frac{1}{n+2}+\cdots+\frac{1}{2n} > \frac{13}{24}$ for $n>1,n\in\Bbb N$

To solve it I used induction but it is leading me nowhere my attempt was as follows:

Lets assume the inequality is true for $n = k$ then we need to prove that it is true for $k+1$

so we need to prove $\frac1{k+2} + \frac1{k+3}+\cdots+\frac1{2(k+1)} > 13/24$

• you want to solve it using induction? Sep 29, 2013 at 9:54
• Yes I think induction would be appropriate Sep 29, 2013 at 9:55
• what is the set of n? does n belongs to Natural numbers greater than 1 ? Sep 29, 2013 at 10:01
• Yes n belongs to Natural numbers greater than 1 Sep 29, 2013 at 10:01
• So what would be a better method? Sep 29, 2013 at 10:08

Using induction we first show this is true for $n=2$:

$\frac{1}{2+1}+\frac{1}{2+2}=\frac{1}{3}+\frac{1}{4}=\frac{7}{12}=\frac{14}{24}\gt\frac{13}{24}$

Therefore it is indeed true for $n=2$.

Now lets assume it is true for some $n=k$, therefore:

$S_k=\frac{1}{k+1}+\frac{1}{k+2}+...+\frac{1}{2k}\gt\frac{13}{24}$

Finally we need to prove that this implies it is also true for $n=k+1$:

$S_{k+1}=\frac{1}{(k+1)+1}+\frac{1}{(k+1)+2}+...+\frac{1}{2(k+1)-2}+\frac{1}{2(k+1)-1}+\frac{1}{2(k+1)}$
$\qquad=\frac{1}{k+2}+\frac{1}{k+3}+...+\frac{1}{2k}+\frac{1}{2k+1}+\frac{1}{2(k+1)}$
$\qquad=-\frac{1}{k+1}+\frac{1}{k+1}+\frac{1}{k+2}+\frac{1}{k+3}+...+\frac{1}{2k}+\frac{1}{2k+1}+\frac{1}{2(k+1)}$
$\qquad=-\frac{1}{k+1}+S_k+\frac{1}{2k+1}+\frac{1}{2(k+1)}$
$\qquad=S_k+\frac{1}{2k+1}+\frac{1}{2(k+1)}-\frac{1}{k+1}$
$\qquad=S_k+\frac{1}{2(2k+1)(k+1)}$
$\qquad\gt S_k$

$\therefore S_{k+1}\gt \frac{13}{24}$

Let $$f(n)=\frac1{n+1}+\frac1{n+2}+\cdots+\frac1{2n}=\sum_{r=1}^{2n}\frac1r-\sum_{s=1}^n\frac1s$$

So, $$f(n+1)-f(n)=\frac1{(2n+1)(2n+2)}>0$$ for integer $n\ge0$

$\displaystyle \implies f(n)$ is an increasing function.

Now, $f(2)=\frac13+\frac14=\frac7{12}>\frac{13}{24}$ as $7\cdot24>12\cdot13$

• I suppose that instead of $\frac 1{n+1}+\frac1{n+2}+\frac1{2n}$ you mean $\frac 1{n+1}+\frac1{n+2}+\ldots+\frac1{2n}$, and instead of $\sum\frac1{2n}$ you mean $\sum_{k=1}^{2n}\frac 1k$, and instead of $\sum\frac1{n}$ you mean $\sum_{k=1}^{n}\frac 1k$? Sep 15, 2016 at 6:38
• @HagenvonEitzen, Thanks Sep 15, 2016 at 6:43
• why f(2) = 1/3+1/4 = 7/12, while f(n) = 1/(n+1)+1/(n+2)+...+1/(2n) Nov 22, 2016 at 22:23

Your sum ($=:S_n$) can be written as follows: $$S_n=-{1\over2n}+\left({1\over 2n}+{1\over n+1}+{1\over n+2}+\ldots+{1\over 4n}\right)+{1\over 4n}\ .$$ Now the large parenthesis can be viewed as a trapezoidal sum for the integral $\int_n^{2n}{1\over x}\ dx=\log 2$. Since the function $x\mapsto{1\over x}$ is convex for $x>0$ the trapezoidal sum is greater than the integral; therefore we immediately obtain $$S_n>\log 2-{1\over 4n}\geq\log2-{1\over8}\doteq0.568\qquad(n\geq2)\ .$$ Since ${13\over24}\doteq0.542$ the claim follows.

$$\lim_{n\to +\infty}\sum_{k=1}^{n}\frac{1}{n+k} = \lim_{n\to +\infty}\frac{1}{n}\sum_{k=1}^{n}\frac{1}{1+\frac{k}{n}} =\lim_{n\to +\infty}\frac{1}{n}\sum_{k=1}^{n}f(\frac{k}{n})=\int_{0}^{1}f(x)dx =\int_{0}^{1}\frac{dx}{1+x}=\log(2)$$

by Reimann's Definite integrals and this is limiting sum and for all terms , the sum is less than $\log(2)$

and $$\log(2)> \frac{13}{24}$$

$$f(n)=\frac{1}{n+1}+\frac{1}{n+2}+\ldots+\frac{1}{2n}=H_{2n}-H_n$$ is an increasing function, since $$f(n+1)-f(n) = \frac{1}{(2n+1)(2n+2)}>0.$$ It follows that $\forall n>1,\; f(n)\geq f(2)=\frac{7}{12}>\frac{13}{24}$.
Additionally, by Riemann sums $$\lim_{n\to +\infty}f(n)=\lim_{n\to +\infty}\sum_{k=1}^{n}\frac{1}{n+k} = \int_{0}^{1}\frac{dx}{1+x}=\log(2)$$ and $$0< \int_{0}^{1}\frac{x^3(1-x)^3}{1+x}\,dx = \frac{111}{20}-8\log(2)$$ leads to $\log(2)<\frac{111}{160}$, so: $$\boxed{ \forall n\geq 2,\quad \color{red}{\frac{7}{12}}\leq\frac{1}{n+1}+\frac{1}{n+2}+\ldots+\frac{1}{2n}<\color{red}{\frac{111}{160}}}$$